2021
DOI: 10.31234/osf.io/gvr2h
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Waiting longer, feeling fatter: Effects of response delay on tactile distance estimation and confidence in females with anorexia nervosa

Abstract: Research suggests that anorexia nervosa (AN) patients overestimate their own body size. However, researchers are divided over whether this overestimation stems from perceptual or non-perceptual differences. In this study, we investigated the influence of non-perceptual factors in tactile size estimation, in a sample of AN patients (N = 30), recovered AN (REC) patients (N = 29) and healthy controls (N=31), by manipulating the role of allowed response time. We further investigated the relationship between allowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…A recent study aimed to experimentally tease apart perceptional and attitudinal influences by manipulating the response time in tactile estimation judgements in AN patients. Results showed that when AN patients were asked to make an immediate tactile judgement (leaving no time to reflect), they showed less overestimations, compared to when AN patients were given five seconds before making their judgement (Engel et al, 2021). This might indicate that perceptional estimates in body size estimation tasks reflect not only an unrealistic metric representation of body size, but also negative cognitive-affective processes.…”
Section: Challenges For Future Researchmentioning
confidence: 91%
“…A recent study aimed to experimentally tease apart perceptional and attitudinal influences by manipulating the response time in tactile estimation judgements in AN patients. Results showed that when AN patients were asked to make an immediate tactile judgement (leaving no time to reflect), they showed less overestimations, compared to when AN patients were given five seconds before making their judgement (Engel et al, 2021). This might indicate that perceptional estimates in body size estimation tasks reflect not only an unrealistic metric representation of body size, but also negative cognitive-affective processes.…”
Section: Challenges For Future Researchmentioning
confidence: 91%
“…Furthermore, adopting implicit measures can help to avoid some of the classic issues related to explicit self-report measures (e.g. demand characteristics), a much debated issue within research into AN (Engel et al, 2021).…”
Section: It Takes Control Of You But It Can Also Feel Very Safe It's a Very Confusing Illnessmentioning
confidence: 99%
“…However, it seems unlikely that one would report seeing themselves as larger when in fact they were simply attending to those parts of their bodies that they judged to be larger. iv For some recent contradictory findings, see (Engel et al, 2021) v This challenge can be formulated more generally: for any BSE task that requires participants to estimate their body size without seeing themselves, participants must rely on an alternative representation of body size. The reconstruction challenge, more generally put, involves the possibility that this representation is distorted by factors distinct from visual perception.…”
Section: Endnotesmentioning
confidence: 99%